2004
DOI: 10.1177/004005990403700104
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Transitions

Abstract: Teachers can enhance their classroom behavior management with explicit instruction and practice in behavioral expectations and routines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Use of a Power Card strategy is not a substitute for solid classroom management. Most students need structure, organization, established routines, behavioral expectations that are taught and reinforced, and consistent classroom procedures (McIntosh & Sanford, 2004). These are all important elements of classroom-based positive behavior support that ensure students learn what is expected of them in classroom environments with maximized learning time (Scheuermann & Hall, 2012).…”
Section: Implications For Classroom Practicementioning
confidence: 99%
“…Use of a Power Card strategy is not a substitute for solid classroom management. Most students need structure, organization, established routines, behavioral expectations that are taught and reinforced, and consistent classroom procedures (McIntosh & Sanford, 2004). These are all important elements of classroom-based positive behavior support that ensure students learn what is expected of them in classroom environments with maximized learning time (Scheuermann & Hall, 2012).…”
Section: Implications For Classroom Practicementioning
confidence: 99%
“…This method effectively diverts students' attention and views directly back to the sound source. This result is relevant to McIntosh's theory that performing sussing is effective during transition (McIntosh et al, 2004). Even though implementing this strategy, the teacher does not get much attention from all students.…”
Section: Sussingmentioning
confidence: 83%
“…Based on research in typically developing children, it has been suggested that limiting time spent on transitions between activities could reduce hyperactivity and increase student engagement as well as time spent on learning activities ( Arlin, 1979 ; Cameron et al, 2005 ; Codding & Smyth, 2008 ). In order to improve efficiency of classroom transitions, teachers may use behavioral strategies as effective instructions, monitoring of child behavior and feedback on (un)desired behavior ( McIntosh et al, 2004 ). For children with ADHD, however, such transitions may also provide opportunities for short moments of movements as they experience difficulties staying seated or being silent ( APA, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…During these transitions, teachers usually provide instructions in multiple steps at once, placing large demands on children’s self-regulation (e.g., switching between tasks). At the same time, children may face delays that may decrease motivation ( Carbone, 2001 ; McIntosh et al, 2004 ; Reid, 1999 ). These demands placed on self-regulation and motivation are expected to result in higher levels of off-task and hyperactive behavior during classroom transitions ( Antrop et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%